Obtenção de filmes poliméricos biodegradáveis para auxiliar no controle do carrapato rhipicephalus microplus - ANJOS, Olga Oliveira dos (2023)
Biodegradable polymeric films can be used in the pharmaceutical, food and agricultural inputs industries. Corn starch (Zea mays L.) is a polysaccharide of natural origin, composed of amylose and amylopectin, with properties for film formation. The high availability of this biopolymer has facilitated its evaluation in research with polymeric films, being associated with natural molecules such as the monoterpenes carvacrol and thymol, the presence of the films can decrease the voltatility of the terpenes, increasing their bioactivity. Carvacrol and thymol have been evaluated as a promising alternative in the control of the cattle tick - a parasite of great economic importance in cattle breeding. Considering the above, the present study aimed to develop corn starch (Zea mays L.) biodegradable films that can optimize the use of monoterpenes in the control of the bovine tick Rhipicephalus microplus. For this, a mixture experimental planning was used, where thirteen polymeric solutions were obtained by gelatinization of corn starch, in composition with glycerol and polyvinyl alcohol (PVOH). The solutions were submitted to the casting technique, resulting in polymeric films. The solutions were characterized for pH and foam percentage. The films were graded on visual appearance, handling (brittle, intermediate or continuous), thickness, morphology, water solubility and biodegradability. The continuous films (BSF-6, BSF-8, BSF-9, BSF-13) were selected and evaluated for their biological activity in larval immersion tests on the tick R. microplus. It was observed that all four solutions formed films on the larvae, leaving them "glued" to each other and lethargic. The previous characterization and the results of tests on larvae allowed the selection of solutions BSF-8 (90% starch + 10% glycerol) and BSF 13 (100% starch) to be associated with the monoterpenes carvacrol and thymol, and subsequently evaluated in immersion tests on larvae at concentrations: 5. 0, 2.5, 1.25, 0.625, 0.313, 0.125 mg/mL of each monoterpene, alone and in association with each film and control groups of 1% ethanol solution and 10% ethanol solution; and in immersion tests on adults of the tick R. microplus, being assigned ten experimental groups (n = 10): 1) carvacrol , 2) film 1 + Carvacrol, 3) film 2 + Carvacrol, 4) thymol, 5) film 1 + thymol, 6) film 2 + thymol, 7) distilled water, 8) 10% ethanol solution, 9) film 1 and 10) film 2 with the concentration of 5.0 mg/ml for each monoterpene. The results showed that carvacrol and thymol showed acaricidal activity on R. micropus larvae with LC50 of 0.765 and 0.691 mg/ml, respectively. Regarding adults, the biodegradable films incorporated with monoterpenes showed significantly lower LC50 composed of carvacrol and thymol alone. The best formulation was film 1 + thymol (CL50 = 0.076 mg/ml), potentiating the effect of thymol by approximately 9.0 times. Carvacrol and thymol at the concentrations tested were effective in controlling engorged females, with percentages of 32.2% and 63.8%, respectively. When incorporated into biodegradable film formulations, these monoterpenes showed much greater efficacy. Film 1 + Carvacrol and film 2 + Carvacrol with control of 71.6% and 97.2%, respectively, while film 1 + thymol and film 2 + thymol formulations showed values of 96.9% and 100.0%. The biopolymer formulations with thymol and carvacrol showed high mortality rates for larvae and engorged females of the tick R. microplus. These results indicate that these formulations have great potential for tick control, mainly due to the percentage of control of up to 100% in females in in vitro tests. Considering the results obtained, this thesis collaborates with research in biotechnology, since polymeric solutions with biodegradable characteristics, obtained from low cost raw material, were formulated for the control of the tick R. microplus.